Pemberdayaan Remaja Jalanan Melalui Program Peta Jalan Pulang Keluarga Untuk Meningkatkan Kemandirian di Pondok Tasawuf Underground Tangerang Selatan - Rosiyani Rosiyani; Muhammad Sahrul (Lembaga Pengembangan Kinerja Dosen, 2024)
The reasons why adolescents fall into the streets vary depending on the individual, with each individual having different problems and needs. Street youth usually earn their income by working on the street from multiple locations, which worsens their situation by creating a negative stigma from the community and uncertainty about their future. Therefore, their empowerment is necessary. The purpose of this research is to achieve an understanding of the roles, stages of the process, as well as the results achieved in the context of empowerment efforts through the Family Return Roadmap program. This research applies a descriptive qualitative approach. The data collection process was conducted through interviews, observation, and documentation. Purposive sampling technique was used to determine relevant informants. The research was conducted at Pondok Tasawuf Underground located in Ciputat Shophouse Complex. The results showed that the empowerment role of Pondok Tasawuf Underground aims to create change for street youth. To achieve this goal, they are given a program that focuses on economic and social aspects, called the Family Return Roadmap, and are supported by adequate facilities to support the implementation of the program. In the stages of the empowerment process, there is a process of forming behavioral awareness, transforming knowledge, and developing intellectual skills. The results of the program implemented in Family Return Roadmap have a positive impact on the economic and social independence of street youth after they participate in the program.